Ambidextrous Leadership in Bureaucratic Reform: A Case Study at Immigration Office Class I Special TPI Surabaya - Zain, R. Dedy Chairil; Suhariadi, Fendy; U, Sendy Ayu Mitra (RSF Conference Series: Business, Management and Social Sciences, 2024)
Surabaya Class I Special TPI Immigration Office won the title of Integrity Zone (ZI) in 2018, Corruption Free Zone (WBK) in 2019, and Clean and Serving Bureaucratic Area (WBBM) in 2020. This WBBM predicate has also been maintained twice. Problems arise with persistently maintaining the title amid current technological developments that require leaders to be creative and innovative while maintaining existing policies. For this reason, an alternative solution is to implement ambidextrous leadership. This research aims to identify the implementation of ambidextrous leadership in a case study at the Surabaya TPI Special Class I Immigration Office. The research method used is qualitative. Data was collected by semi-structured interviews with 50 respondents at the executive level in the general, analyst, and examiner sections. Data analysis used thematic techniques, such as classifying data into several sections and then generalizing to get a comprehensive picture. The results showed that ambidextrous leadership was identified in three areas of bureaucratic reform, namely (1) the management area, (2) the HR management system, and (3) the area of improving the quality of public services.